Functional Characterization of an Amaranth Natterin-4-Like-1 Gene in Arabidopsis thaliana - Cabrales-Orona, Gabriela; Martínez-Gallardo, Norma; Délano-Frier, John Paul (Frontiers in Sustainable Food Systems, 2022)
The functional characterization of an Amaranthus hypochondriacus Natterin-4-Like-1 gene (AhN4L-1) coding for an unknown function protein characterized by the presence of an aerolysin-like pore-forming domain in addition to two amaranthin-like agglutinin domains is herewith described. Natterin and nattering-like proteins have been amply described in the animal kingdom. However, the role of nattering-like proteins in plants is practically unknown. The results described in this study, obtained from gene expression data in grain amaranth and from AhN4L-1-overexpressing Arabidopsis thaliana plants indicated that this gene was strongly induced by several biotic and abiotic conditions in grain amaranth, whereas data obtained from the overexpressing Arabidopsis plants further supported the defensive function of this gene, mostly against bacterial and fungal plant pathogens. GUS and GFP AhN4L-1 localization in roots tips, leaf stomata, stamens and pistils also suggested a defensive function in these organs, although its participation in flowering processes, such as self-incompatibility and abscission, is also possible. However, contrary to expectations, the overexpression of this gene negatively affected the vegetative and reproductive growth of the transgenic plants, which also showed no increased tolerance to salinity and water-deficit stress. The latter despite the maintenance of significantly higher chlorophyll levels and photosynthetic parameters under intense salinity stress. These results are discussed in the context of the physiological roles known to be played by related lectins and AB proteins in plants.